Mode locked erbium doped fiber laser using zinc oxide thin film as saturable absorber / Ibrahim Abdulrahman Mahmood - Ibrahim Abdulrahman, Mahmood (2018)
Mode locked fiber lasers have attracted a great research interest in recent years due to their applications in many areas such as material processing, remote sensing, optical clock technology and ultrahigh-speed optical communications. Compared with Q-switched fiber lasers, they have the advantages of higher repetition rate, higher peak power, wider spectral range and shorter pulse width. Zinc oxide (ZnO) has also been identified as an ideal saturable absorber (SA) due to its high nonlinear optical response, high sustainability to damage threshold and fast recovery time. In this work, for the first time, two types of mode locked erbium doped fiber lasers (EDFLs) have been experimentally demonstrated using ZnO as SA. At first, the ZnO fabricated into a thin film using a seeding solution mixed with Polyvinyl Alcohol (PVA), was integrated into an EDFL cavity with 201.5 m long optical resonator. Self-started mode locked pulses of 400 ns pulse width was successfully realized at a relatively low pump power of 45.4 mW with the fundamental frequency of 993 kHz. The laser operated at a central wavelength of 1558.34 nm with the pulse energy of 11.6 nJ and peak power of 27.3 mW are obtained at the maximum pump power of 142 mW. The same ZnO SA film was also integrated into another EDFL cavity with a shorter length of 61.5 m. At a pump power of 42 mW, self- started mode locked pulses train was also successfully generated with a much higher repetition rate and much shorter pulse width of 3.26 MHz and 1.76 ps, respectively. The laser operates at a longer wavelength of 1599.5 nm. The pulse energy and peak power of the laser output were 2.16 nJ and 1.14 kW respectively at the maximum pump power of 159 mW while the average output power was obtained at 6.91 mW. This finding indicates that ZnO thin film is a promising SA material for a demonstration of mode locked EDFL, which may find suitable applications in the emerging optical communication system. Keywords: fiber laser, mode locking, saturable absorber, Zinc Oxide thin film.